2010
DOI: 10.1097/mnm.0b013e3283407950
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution and radiation dosimetry of the hypoxia marker 18F–HX4 in monkeys and humans determined by using whole-body PET/CT

Abstract: Objectives-18 F-HX4 is a novel positron emission tomography (PET) tracer for imaging hypoxia. The purpose of this study was to determine the biodistribution and estimate the radiation dose from 18 F-HX4 using whole body PET/CT scans in monkeys and humans.Methods-Successive whole body PET/CT scans were performed following the injection of 18 F-HX4 to four healthy humans (422 ± 142 MBq) and to three rhesus monkeys (189 ± 3 MBq). Biodistribution was determined from PET images and organ doses were estimated using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 15 publications
(16 reference statements)
3
32
0
Order By: Relevance
“…[ 18 F]HX4 biodistribution in normal tissues was found to be fast and homogeneous, as has already been published for [ 18 (16). This is, however, not surprising, because the highest [ 18 F]HX4 uptake was found in the urinary bladder, confirming excretion primarily through the kidneys.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…[ 18 F]HX4 biodistribution in normal tissues was found to be fast and homogeneous, as has already been published for [ 18 (16). This is, however, not surprising, because the highest [ 18 F]HX4 uptake was found in the urinary bladder, confirming excretion primarily through the kidneys.…”
Section: Discussionsupporting
confidence: 80%
“…This is, however, not surprising, because the highest [ 18 F]HX4 uptake was found in the urinary bladder, confirming excretion primarily through the kidneys. To reduce bladder and kidney dose, patients should therefore be encouraged to maintain adequate hydration and void frequently (15,16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite being similar physiology to humans, human effective dose using monkey data could be either underestimated or overestimated. For example, the effective dose of hypoxia marker 18 F-HX4 estimated from monkey study is significantly higher (42 µSv/MBq) than the results obtained from humans (27 µSv/MBq) [30]. Moreover, although we do not expect that the anesthesia affects the biodistribution and metabolism of 64 Cu-BaBaSar-RGD 2 , it has been found that different anesthetic protocols can result a significant effect on the uptake of many organs [31].…”
Section: Discussionmentioning
confidence: 66%
“…18 F-FAZA imaging provides similar hypoxia information to 18 F-FMISO, which may be helpful for therapy planning [96]. In addition, Lehtiö et al [97] [103,104]. Cu(II)-ATSM, a neutral lipophilic molecule, is another alternative PET probe for hypoxia imaging based on a metal complex of radioactive copper with ATSM, diacetylbis(N4-methylthiosemicarbazone), which is highly membrane permeable.…”
Section: Hypoxia Pet Imagingmentioning
confidence: 99%